Contested frontiers: indigenous mobilization and control over land and natural resources in Myanmar's upland areas - Einzenberger, Rainer (2016)
Abstract: "Over the past two decades, Myanmar's upland areas have gradually turned into formally administered, legible, and governable state-territory. Following decades of armed conflict, a series of ceasefire agreements since the 1990s opened the door for the central state's expansion of territorial control in the upland areas through the exploitation of natural resources and land concessions. New civil society coalitions are being formed inside Myanmar to resist the states strategy of accumulation by dispossession in conjunction with enclosures and the formation of state territory. This paper provides a brief outline of an ongoing research project which takes a socio-spatial perspective on state building processes and links the concept of the resource frontier with emerging discourses on indigenous rights in Myanmar." (author's abstract)